2004
DOI: 10.1111/j.1440-1738.2003.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Petrochemical evidence for off‐ridge magmatism in a back‐arc setting from the Yakuno ophiolite, Japan

Abstract: The Permian ophiolite emplaced in the Yakuno area, Kyoto Prefecture, consists of metavolcanic sequences, metagabbro and a troctolitic intrusion. The metavolcanics are associated with thick mudstone through a contact that shows the flowage of lava over unconsolidated mud layers on the sea floor. The metavolcanics and metagabbro have rare earth element (REE) patterns that are similar to enriched (E)-and transitional (T)-types ([La/Yb] N = 0.77-11.2) of mid-oceanic ridge basalts (MORB), whereas their Nb/La ratios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 46 publications
0
11
0
1
Order By: Relevance
“…The Tamba Belt was thrust by the Permian Ultra‐Tamba accretionary complex, which was in turn thrust by the Permian Yakuno ophiolite (Maizuru Belt) originated in an island arc – marginal basin system (e.g. Ichiyama & Ishiwatari 2004; Osozawa et al . 2004; Suda 2004).…”
Section: Geological Settingmentioning
confidence: 99%
“…The Tamba Belt was thrust by the Permian Ultra‐Tamba accretionary complex, which was in turn thrust by the Permian Yakuno ophiolite (Maizuru Belt) originated in an island arc – marginal basin system (e.g. Ichiyama & Ishiwatari 2004; Osozawa et al . 2004; Suda 2004).…”
Section: Geological Settingmentioning
confidence: 99%
“…Ichiyama and Ishiwatari [11] suggested that the Yakuno ophiolite in the Yakuno-cho area (Figure 1) originated from a BAB crust, consisting of metabasalt and metagabbro of BAB affinities and a minor amount of troctolite.…”
Section: Yakuno Ophiolite In Oshima Peninsula Ayabe Andmentioning
confidence: 99%
“…Data sources for the mafic rocks in Yakuno ophiolite are excerpted from Suda and Hayasaka [7] and Ichiyama and Ishiwatari [11]. The metagabbros in Yakuno ophiolite plotted in this diagram were evaluated to be the melt origin which do not possess the cumulite compositions by Suda and Hayasaka [7].…”
Section: Geochemical Implications For the Evolution Of Babbmentioning
confidence: 99%
See 1 more Smart Citation
“…1a). At least three different segments have been recognized according to their petrogenetic features: (1) an unusually thick oceanic crust mantle section; (2) island arc type crust; and, (3) back arc basin oceanic crust as a basement of the Permian Maizuru Group (Ishiwatari, 1985(Ishiwatari, , 1999Koide, 1986;Hayasaka, 1990;Ishiwatari et al, 1990;Ichiyama and Ishiwatari, 2003). The Asago body, 10 13 km in size, occurs as a fault bounded slice that tectonically overlays the Late Permian accretionary complex of the Ultra Tanba Terrane (Fig.…”
mentioning
confidence: 99%